NEOGEOGRAPHY AND SEISMIC RISK PERCEPTION. A COMPARISON BETWEEN TWO CASE STUDIES: CALABRIA, SOUTHERN ITALY AND MALTA - Francesco DE PASCALE; Marcello BERNARDO; Francesco MUTO; Sebastiano D’AMICO; Rosarianna ZUMBO; Pauline GALEA; Matthew AGIUS (European Journal of Geography)
Geography of perception aims at clarifying human behaviour by studying the concepts and images of the real world that a person elaborates on by considering the psychological and social aspects of man’s behaviour within an environment. In this context, a questionnaire was given to primary and middle school pupils in an area of Calabria (Southern Italy), which has recently been affected by an on-going seismic sequence widely felt by the local population. The same questionnaire was given to students in Malta (Central Mediterranean), an area considered to have a low-to-moderate seismic hazard, and where earthquake awareness is not culturally strong. In this way, the knowledge effectively possessed by the students (relating to age, experience and area of origin) are analysed; their analogous and differing perceptions on earthquakes in different areas are highlighted. The data collected can be used to project and create new informative tools through which students will become “geographic information volunteers” studying natural risks such as earthquakes, and augmenting the territory’s level of resilience.